Effects of toll like receptor 4 (TLR4) and toll like receptor 2 (TLR 2) gene polymorphisms on clinical outcomes in acute non-biliary pancreatitis patients - Anılır, Ender; Özen, Filiz; Yıldırım, İbrahim Halil (Frontiers in Immunology, 2024)
In this retrospective study, it was aimed to evaluate effects of Toll Like Receptor 4 (TLR4) and Toll Like Receptor 2 (TLR 2) gene polymorphisms on clinical outcomes in acute nonbiliary pancreatitis patients.Methods: A total of 108 acute non-biliary pancreatitis patients (ANBP) were retrospectively subjected to the study. Gender, age, number of attacks, hospitalization duration, amylase, lipase, aspartate aminotransferase (AST), alanine aminotransferase (ALT), leukocyte, C-reactive protein (CRP), total bilirubin, direct bilirubin, Atlanta score, ultrasonography (USG), Computer Tomography (CT) and patient outcome differences between TLR 4 Rs4986790, TLR 4 Rs4986791 and TLR 2 groups were evaluated.Results: According to TLR 4 Rs4986790 groups, females were significantly common in AA sequence (AA) group with statistically significant difference (p<0.05). Leukocyte mean of AG sequence (AG) group was significantly higher than of AA group (p<0.05). All parameter differences between TLR 4 Rs4986791 and TLR 2 groups were statistically insignificant (p>0.05). there was a statistically significant correlation between TLR 4 Rs4986790 and gender (r=0.265; p<0.01), Leukocyte (r=0.200; p<0.05) and Pseudocyst (r=0.203; p<0.05). TLR 4 Rs4986790 gene polymorphism had significant effect on leukocyte level in acute non-biliary pancreatitis patients (OR: -0.1.900; p<0.05). Predictive value of leukocyte for TLR 4 Rs4986790 was statistically significant (Area Under Curve: 0.624; p<0.05). For 7.65 leukocyte cut off value, sensitivity for AA gene polymorphism was 84.2% and specificity was 40.5% Conclusion: Although the clinical and outcome parameters of ANBP patients in terms of TLR 4 Rs4986791 and TLR 2 do not show significant differences, research findings point to the diagnostic value of patients' leukocyte parameters in determining TLR-4 Rs4986790 ploimorphism groups.